Implementasi Bisnis dan Potensi Keberlanjutan Fusion Katsu sebagai Inovasi Kuliner di Kota Palembang - Maria Selviana Arifin; Valent Fransiska Wijaya; Nyimas Artina (Universitas Multi Data Palembang, 2026)
This study describes the business implementation and sustainability potential of Fusion Katsu as a culinary innovation in Palembang City. The scope of the study focuses on operational implementation, consumer response, and sustainability strategies applied in running the business. A descriptive approach was used, supported by survey data collected through observation, documentation, and online questionnaires distributed to consumers. The results indicate that Fusion Katsu has been implemented effectively through a pre-order system and offline sales at the university campus, which help maintain product quality and operational efficiency. Consumer responses show a high level of interest, particularly among students and young consumers, due to affordable pricing, practical packaging, and attractive product presentation. In conclusion, Fusion Katsu demonstrates good potential for business sustainability, supported by positive market acceptance and planned business development strategies